Insulating plastic material

By adding micro-carbonized wood fibers to polystyrene and polypropylene blend materials and using specific heating and dispersion technologies, the compatibility problems in the blend materials are solved, significantly improving the insulation performance and interface bonding effect.

CN119529424AInactive Publication Date: 2025-02-28HUIZHOU WANLU PLASTIC PROD CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411792198.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When polystyrene and polypropylene are blended, there are compatibility issues, resulting in limited product performance improvement.

Method used

The interface compatibility between polypropylene and polystyrene is improved by adding microcarbonized wood fibers and using a three-stage heating process and ultrasonic dispersion technology.

Benefits of technology

The insulation performance and interface combination effect of polypropylene and polystyrene blend materials are significantly improved, ensuring the stability and controllability of product performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of polymer plastic materials. The invention relates to an insulating plastic material, in particular to an insulating plastic material. The product prepared by the invention comprises the following raw materials in parts by weight: 100-110 parts of polypropylene, 20-25 parts of polystyrene and 6-8 parts of micro-carbonized wood fiber. The preparation method of the micro-carbonized wood fiber comprises the following steps: cleaning bagasse, drying, crushing, and sieving with a 80-120-mesh sieve to obtain crushed bagasse; the preparation method comprises the following steps: ultrasonically dispersing crushed bagasse in water, adding ethyl orthosilicate which is 8-10% of the mass of the crushed bagasse, carrying out hydrolysis reaction, filtering, washing and drying to obtain a precursor; and slowly heating the precursor to 300-320 DEG C at the rate of 0.1-0.2 DEG C / min in an inert atmosphere, carrying out heat preservation micro-carbonization treatment for 6-24 hours, and discharging to obtain the micro-carbonized wood fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polymer plastic materials, and more specifically, relates to an insulating plastic material. Background Art

[0002] For polyethylene or polypropylene plastic materials, many researchers are committed to modifying them to improve their insulation properties. Blending modification is a low-cost and practical modification method. At present, there are many polymers that can improve the insulation properties of polyethylene or polypropylene, such as POE, PS and HDPE. For example, some scholars have found that when LDPE is blended with MPE, when the addition amount of MPE is 1%, the DC breakdown strength can be increased by 19.9%, and the accumulation of space charge can be effectively reduced. This is mainly due to the formation of imperfect spherulites and the increase in crystallinity, which leads to an increase in charge mobility.

[0003] However, during the blending modification process, the inventors found that many polymers are difficult to be compatible with each other. In this case, the structural inhomogeneity and instability of the product after blending will lead to uncontrollable product performance and unreliability during use. Based on this, simple physical blending cannot effectively bring out the advantages of two or more polymers.

[0004] Specifically, blending polystyrene with polyethylene or polypropylene is an optional solution. First, polystyrene itself is an excellent insulating material because the benzene ring has the characteristic of dissipating high-energy electron energy, and under high DC voltage, there is almost no spatial charge accumulation inside the polystyrene material. However, simply blending polyolefin materials such as polyethylene or polypropylene with polystyrene is prone to incompatibility problems. Therefore, how to improve the compatibility of the two so that the comprehensive performance of the product can be effectively exerted is one of the technical problems still faced by those skilled in the art. Summary of the invention

[0005] The technical problem to be solved by the present invention is that, for insulating plastic materials, although relatively better insulating properties can be obtained when polystyrene and polypropylene are blended, there is a problem of compatibility between the two when the two are simply physically blended, which results in limited improvement in product performance. Based on the above problem, the present invention provides an insulating plastic material.

[0006] The object of the present invention is to provide an insulating plastic material.

[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0008] An insulating plastic material comprises the following raw materials in parts by weight:

[0009] 100-110 parts of polypropylene, 20-25 parts of polystyrene, 6-8 parts of micro-carbonized wood fiber;

[0010] The preparation steps of the micro-carbonized wood fiber include:

[0011] After washing the bagasse, drying, crushing, and passing through an 80-120 mesh sieve, bagasse crushed material is obtained;

[0012] Ultrasonic dispersion of bagasse crushed materials in water, and then adding 8-10% of the weight of bagasse crushed materials with ethyl orthosilicate, after hydrolysis reaction, filtering, washing and drying to obtain a precursor;

[0013] In an inert atmosphere, the precursor is slowly heated to 300-320° C. at a rate of 0.1-0.2° C. / min, and after being kept warm for 6-24 hours for micro-carbonization treatment, the material is discharged to obtain micro-carbonized wood fiber.

[0014] In the above technical solution, micro-carbonized wood fibers prepared by the above method are added to improve the interface compatibility between polypropylene and polystyrene. Specifically, the above technical solution uses bagasse crushed materials as raw materials, and after preliminary crushing, a certain amount of tetraethyl orthosilicate is coated on the surface thereof. In this process, the amount of tetraethyl orthosilicate needs to be strictly controlled. If the amount of tetraethyl orthosilicate is too little, it is easy to cause the surface of the wood fiber after micro-carbonization to be too smooth and the density to be relatively low. If the surface is too smooth, then during the processing, the molecular chains of the polystyrene fiber and the polypropylene fiber after melting are difficult to interact with the silica particles deposited on the surface of the wood fiber. For example, after melting, the molecular chains of the polymer resin stretch. During the blending process, the molecular chains of the two are easily entangled with the wood fibers. During the entanglement process, the presence of an appropriate amount of silica particles on the surface can form a discontinuous island distribution. The adjacent different "islands" can serve as stress concentration points to reinforce the entanglement, thereby improving the interface bonding effect; if the density is relatively low, then during the processing, the micro-carbonized wood fibers are easy to float to the surface of the system and are difficult to disperse evenly in the system; if the amount of ethyl orthosilicate is too much, the discontinuous island distribution will gradually become a continuously distributed coating layer, or the micro-carbonized wood fibers will be too dense and settle during the processing;

[0015] The reason why the heating rate needs to be controlled to be slow during the carbonization process is that, in the process of relatively low heating, the bagasse fiber can be slowly pyrolyzed. Due to the gradual generation of shrinkage stress due to internal pyrolysis, the island-shaped silica coating on the surface can provide a certain support force at the coating point, thereby causing the bagasse fiber to gradually twist. If the heating rate is too fast, the stress will be released too quickly, which will easily lead to excessive twisting of the bagasse fiber and local excessive entanglement of itself. After excessive entanglement of itself, it will significantly affect its uniform dispersion in the system.

[0016] During the carbonization process, the carbonization temperature of about 300-320℃ will cause the bagasse fiber to be slightly carbonized, and the moisture, volatile organic matter, etc. will be decomposed, but the organic matter is not completely decomposed, so that there are still certain active functional groups on the surface of the bagasse fiber, making it compatible with polystyrene, that is, polyethylene resin.

[0017] Furthermore, the hydrolysis reaction includes heat preservation and hydrolysis reaction for 3-5 hours at a pH of 5.6-6.2, a temperature of 60-65° C., and a stirring rate of 60-80 r / min.

[0018] By controlling the hydrolysis conditions, specifically, hydrolyzing ethyl orthosilicate under acidic conditions and controlling the hydrolysis temperature, the hydrolysis process of ethyl orthosilicate can be made slow and controllable. Once hydrolysis products are formed, they can be adsorbed and fixed on the surface of bagasse fibers, thus avoiding rapid hydrolysis that causes the hydrolysis products to agglomerate themselves.

[0019] Furthermore, the heat preservation micro-carbonization treatment time is 12-14 hours.

[0020] Furthermore, the preparation step of the micro-carbonized wood fiber also includes:

[0021] After soaking the bagasse in water, taking it out, and then letting it stand for natural fermentation for 5-10 days at a temperature of 35-40°C and a relative humidity of 80-85%, and then washing it with water, heating it to boil, and filtering it to obtain pretreated bagasse;

[0022] Before the bagasse fiber is pyrolyzed, natural fermentation treatment is adopted. In the appropriate temperature and humidity environment, the residual sugars and other nutrients in the bagasse can cause a certain degree of fermentation. During the fermentation process, the bagasse fiber begins to become loose and activated, which will be conducive to the effective deposition of ethyl orthosilicate in the subsequent process.

[0023] The pretreated bagasse is washed, dried, crushed, and passed through a 80-120 mesh sieve to obtain bagasse crushed material;

[0024] Ultrasonic dispersion of bagasse crushed materials in water, and then adding 8-10% of the weight of bagasse crushed materials with ethyl orthosilicate, after hydrolysis reaction, filtering, washing and drying to obtain a precursor;

[0025] In an inert atmosphere, the precursor is slowly heated to 300-320° C. at a rate of 0.1-0.2° C. / min, and after being kept warm for 6-24 hours for micro-carbonization treatment, the material is discharged to obtain micro-carbonized wood fiber.

[0026] Furthermore, the insulating plastic material further comprises polyoxymethylene resin having a mass of 0.6-0.8 times that of the polystyrene;

[0027] Furthermore, when preparing the insulating plastic material, the raw materials are first mixed, heated to 158-160° C., high-viscosity blending for 10-12 minutes, then heated to 170-175° C., medium-viscosity blending for 4-6 minutes, and then heated to 215-220° C., low-viscosity blending for 10-15 minutes.

[0028] After the introduction of polyformaldehyde resin, the three-stage heating process was further controlled during the material blending process. Specifically, the heating temperature of the first stage was close to the melting temperature of polypropylene resin, but lower than the melting temperatures of polystyrene and polyformaldehyde. Under this condition, the system has a higher viscosity. Under high viscosity conditions, the interaction force between the micro-carbonized wood fiber polymer molecular chains is the largest, so that a strong mutual friction can be formed between the two, which is conducive to the good dispersion of the micro-carbonized wood fiber in the resin system; then it was not heated to the highest melting temperature in one step, that is, the melting temperature of polystyrene, but was pre-heated to the melting temperature of polyformaldehyde, so that the interaction force between different resin molecular chains can also have a process of full release, that is, during medium-viscosity blending, the polyformaldehyde molecular chain can be well dispersed in the system after stretching; it avoids heating to the highest temperature at one time, and after all the polymer chains in the system are stretched, it is difficult for the polymer resin to form a strong mutual entanglement force with the micro-carbonized wood fiber.

[0029] Furthermore, the insulating plastic material further includes an auxiliary agent in an amount of 4-6% by mass of the polypropylene;

[0030] The auxiliary agent comprises the following raw materials in parts by weight:

[0031] 10-15 parts of lubricant, 15-20 parts of antioxidant, 20-25 parts of antioxidant, 30-35 parts of plasticizer;

[0032] Wherein, the lubricant is selected from any one of calcium stearate, magnesium stearate and zinc stearate;

[0033] The antioxidant is selected from any one of antioxidant 4010, antioxidant RD, antioxidant MB, antioxidant D, antioxidant AW, and antioxidant BLE;

[0034] The antioxidant is selected from any one of antioxidant BHT, antioxidant 801, butylated hydroxytoluene, and thiobis(3-methyl-6-tert-butyl)phenol;

[0035] The plasticizer is selected from any one of tributyl citrate, epoxy soybean oil, dicyclohexyl phthalate, glycerol tribenzoate or trimethylolpropane tribenzoate.

[0036] Furthermore, the insulating plastic material further includes organic bentonite in an amount 0.4-0.6 times the mass of the micro-carbonized wood fiber;

[0037] Furthermore, when preparing the insulating plastic material, the steps include:

[0038] First, the organic bentonite and the carbonized wood fiber are mixed and poured into water, and then ultrasonically treated for 40-60 minutes at an ultrasonic frequency of 200-220 kHz, and then filtered, washed, dried, passed through a 500-mesh sieve, and the finer particles under the sieve are sieved out to obtain the residue on the sieve to obtain a blend;

[0039] After mixing the blend, polypropylene and polystyrene, heat to 158-160°C, blend for 10-12 minutes at high viscosity, then heat to 170-175°C, blend for 4-6 minutes at medium viscosity, then continue to heat to 215-220°C, blend for 10-15 minutes at low viscosity.

[0040] The introduction of organic bentonite can further improve the dispersion uniformity of carbonized wood fiber in the three-stage temperature rising blending process. This is because, although the polymer resin molecular chain has a strong interaction with it during the high-viscosity blending process, the interaction is too strong, which can easily cause the silica particles adsorbed on the surface to fall off, thereby making the entanglement effect ineffective, and the detached silica particles are also difficult to disperse evenly in the system. The inventors found that if an appropriate amount of organic bentonite is added, its layered structure can slip to a certain extent during the high-viscosity blending process, thereby alleviating the concentration of stress on a single carbonized wood fiber and significantly reducing the shedding of silica particles. DETAILED DESCRIPTION

[0041] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0042] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0043] Example 1

[0044] After soaking the bagasse in water, taking it out, draining the water, and then standing it for natural fermentation for 5 days at a temperature of 35°C and a relative humidity of 80%, then washing it with water for 3 times, heating and boiling it for 10 minutes, and filtering it to obtain the pretreated bagasse;

[0045] The pretreated bagasse is washed, dried at 100°C to constant weight, crushed, and passed through an 80-mesh sieve to obtain bagasse crumbs;

[0046] The bagasse crushed material and water were mixed at a mass ratio of 1:10, and ultrasonically dispersed for 20 minutes at an ultrasonic frequency of 60kHz, and then 8% of the weight of the bagasse crushed material was added with tetraethyl orthosilicate. The mixture was subjected to a hydrolysis reaction at a pH of 5.6, a temperature of 60°C, and a stirring rate of 60r / min for 3 hours, and then filtered, the filter cake was collected, and the filter cake was washed and dried to obtain a precursor.

[0047] In an inert atmosphere, the precursor is slowly heated to 300°C at a rate of 0.1°C / min, and after being kept for micro-carbonization treatment for 12 hours, the material is discharged to obtain micro-carbonized wood fiber;

[0048] By weight, take 100 parts of polypropylene, 20 parts of polystyrene, and 6 parts of micro-carbonized wood fiber;

[0049] Furthermore, 4% of the mass of polypropylene as an auxiliary agent and 0.6 times the mass of polystyrene as polyoxymethylene resin are taken;

[0050] The auxiliary agent comprises the following raw materials in parts by weight:

[0051] 10 parts of lubricant, 15 parts of antioxidant, 20 parts of antioxidant, 30 parts of plasticizer;

[0052] Wherein, the lubricant is selected from calcium stearate;

[0053] The antioxidant is selected from antioxidant 4010;

[0054] The antioxidant is selected from the antioxidant BHT;

[0055] The plasticizer is selected from tributyl citrate;

[0056] First, carbonized wood fiber and organic bentonite in an amount of 0.4 times the mass of the carbonized wood fiber are mixed and poured into water, wherein the amount of water used is 12 times the mass of the carbonized wood fiber, and then ultrasonically treated for 40 minutes at an ultrasonic frequency of 200 kHz, and then filtered, washed, dried, passed through a 500-mesh sieve, and finer particles under the sieve are sieved out to obtain the residue on the sieve to obtain a blend;

[0057] The blend, polypropylene, polystyrene, polyoxymethylene resin and additives were mixed and poured into a torque rheometer, heated to 158°C, high viscosity blending for 10 minutes, then heated to 170°C, medium viscosity blending for 4 minutes, then continued to heat to 215°C, low viscosity blending for 10 minutes, and then hot pressed for 15 minutes at a temperature of 180°C and a pressure of 15 MPa on a flat vulcanizer to obtain an insulating plastic material sample.

[0058] Example 2

[0059] After soaking the bagasse in water, taking it out, draining the water, and then standing it for natural fermentation for 8 days at a temperature of 38°C and a relative humidity of 82%, it was then washed with water for 3 times, heated and boiled for 12 minutes, and filtered to obtain the pretreated bagasse;

[0060] The pretreated bagasse is washed, dried at 100°C to constant weight, crushed, and passed through a 100-mesh sieve to obtain bagasse crumbs;

[0061] The bagasse crushed material and water were mixed at a mass ratio of 1:10, and ultrasonically dispersed for 20 minutes at an ultrasonic frequency of 60kHz, and then 9% of the weight of the bagasse crushed material was added with tetraethyl orthosilicate, and the mixture was kept at a pH of 5.8, a temperature of 62°C, and a stirring rate of 70r / min for a hydrolysis reaction for 4 hours, and then filtered, the filter cake was collected, and the filter cake was washed and dried to obtain a precursor;

[0062] In an inert atmosphere, the precursor was slowly heated to 310°C at a rate of 0.1°C / min, and after being kept for micro-carbonization treatment for 13 hours, the material was discharged to obtain micro-carbonized wood fiber;

[0063] By weight, take 105 parts of polypropylene, 22 parts of polystyrene, and 7 parts of micro-carbonized wood fiber;

[0064] Furthermore, 5% of the mass of polypropylene as an auxiliary agent and 0.7 times the mass of polystyrene as polyoxymethylene resin are taken;

[0065] The auxiliary agent comprises the following raw materials in parts by weight:

[0066] 12 parts lubricant, 18 parts antioxidant, 22 parts antioxidant, 33 parts plasticizer;

[0067] Wherein, the lubricant is selected from magnesium stearate;

[0068] The antioxidant is selected from antioxidant RD;

[0069] The antioxidant is selected from antioxidant 801;

[0070] The plasticizer is selected from epoxidized soybean oil;

[0071] First, carbonized wood fiber and organic bentonite in an amount of 0.5 times the mass of the carbonized wood fiber are mixed and poured into water, wherein the amount of water used is 12 times the mass of the carbonized wood fiber, and then ultrasonically treated for 50 minutes at an ultrasonic frequency of 210 kHz, and then filtered, washed, dried, passed through a 500-mesh sieve, and finer particles under the sieve are sieved out to obtain the residue on the sieve to obtain a blend;

[0072] The blend, polypropylene, polystyrene, polyoxymethylene resin and additives were mixed and poured into a torque rheometer, heated to 159°C, high viscosity blending for 11 minutes, then heated to 172°C, medium viscosity blending for 5 minutes, and then continued to heat to 218°C, low viscosity blending for 12 minutes, and then hot pressed for 15 minutes at a temperature of 180°C and a pressure of 15 MPa on a flat vulcanizer to obtain an insulating plastic material sample.

[0073] Example 3

[0074] After soaking the bagasse in water, taking it out, draining the water, and then standing it for natural fermentation for 10 days at a temperature of 40°C and a relative humidity of 85%, then washing it with water for 3 times, heating and boiling it for 15 minutes, and filtering it to obtain the pretreated bagasse;

[0075] The pretreated bagasse is washed, dried at 100°C to constant weight, crushed, and passed through a 120-mesh sieve to obtain bagasse crumbs;

[0076] The bagasse crushed material and water were mixed at a mass ratio of 1:10, and ultrasonically dispersed for 20 minutes at an ultrasonic frequency of 60kHz, and then 10% of the weight of the bagasse crushed material of ethyl orthosilicate was added, and the mixture was hydrolyzed for 5 hours at a pH of 6.2, a temperature of 65°C, and a stirring rate of 80r / min. The mixture was filtered, the filter cake was collected, and the filter cake was washed and dried to obtain a precursor;

[0077] In an inert atmosphere, the precursor was slowly heated to 320°C at a rate of 0.2°C / min, and after being kept for micro-carbonization treatment for 14 hours, the material was discharged to obtain micro-carbonized wood fiber;

[0078] By weight, take 110 parts of polypropylene, 25 parts of polystyrene, and 8 parts of micro-carbonized wood fiber;

[0079] Furthermore, 6% of the mass of polypropylene as an auxiliary agent and 0.8 times the mass of polystyrene as polyoxymethylene resin are taken;

[0080] The auxiliary agent comprises the following raw materials in parts by weight:

[0081] 15 parts of lubricant, 20 parts of antioxidant, 25 parts of antioxidant, 35 parts of plasticizer;

[0082] Wherein, the lubricant is selected from zinc stearate;

[0083] The antioxidant is selected from antioxidant D;

[0084] The antioxidant is selected from butylated hydroxytoluene;

[0085] The plasticizer is selected from dicyclohexyl phthalate;

[0086] First, carbonized wood fiber and organic bentonite in an amount of 0.6 times the mass of the carbonized wood fiber are mixed and poured into water, wherein the amount of water used is 12 times the mass of the carbonized wood fiber, and then ultrasonically treated for 60 minutes at an ultrasonic frequency of 220 kHz, and then filtered, washed, dried, passed through a 500-mesh sieve, and finer particles under the sieve are sieved out to obtain the residue on the sieve to obtain a blend;

[0087] The blend, polypropylene, polystyrene, polyoxymethylene resin and additives were mixed and poured into a torque rheometer, heated to 160°C, high viscosity blended for 12 minutes, then heated to 175°C, medium viscosity blended for 6 minutes, then continued to heat to 220°C, low viscosity blended for 15 minutes, and then hot pressed for 15 minutes at a temperature of 180°C and a pressure of 15 MPa on a flat vulcanizer to obtain an insulating plastic material sample.

[0088] Example 4

[0089] The present embodiment differs from the embodiment 1 in that the heat preservation micro-carbonization treatment time is 6 hours. Although a shorter time may result in lower energy loss, the sufficiency of the pyrolysis is limited. If the time is shorter, it will be difficult to volatilize the organic volatiles, which will affect the uniform dispersion of the material in the system.

[0090] Example 5

[0091] The present embodiment differs from the embodiment 1 in that the heat preservation micro-carbonization treatment time is 24 hours. Too long a time will lead to a significant increase in energy consumption. Although a more sufficient carbonization effect can be obtained, if the time is extended further, the gain effect on the product begins to be discounted, and the energy consumption loss is significant.

[0092] Example 6

[0093] The present embodiment differs from the embodiment 1 in that no polyoxymethylene resin is added and the other conditions remain unchanged.

[0094] Example 7

[0095] Compared with Example 1, this embodiment differs in that no organic bentonite is added, and other conditions remain unchanged.

[0096] Comparative Example 1

[0097] The difference between this comparative example and Example 1 is that the carbonization temperature is adjusted to 500° C., and the other conditions remain unchanged.

[0098] Too high a carbonization temperature will cause the bagasse fiber to be fully carbonized. After adding it to the system, the fully carbonized bagasse fiber will have conductivity, which will lead to a decrease in the insulation performance of the product; it does not meet the basic requirements of insulation products, but the mechanical properties of the product will not decrease significantly.

[0099] Comparative Example 2

[0100] The difference between this comparative example and Example 1 is that the heating rate is adjusted to 3° C. / min, and the other conditions remain unchanged.

[0101] Comparative Example 3

[0102] The difference between this comparative example and Example 1 is that no ethyl orthosilicate is added, and the other conditions remain unchanged.

[0103] The performance of the products obtained in the above examples and comparative examples was tested, and the specific test methods and test results are as follows:

[0104] Referring to GB / T 1040-1992, the tensile properties of the product were tested. The specific test results are shown in Table 1.

[0105] According to GB / T 1043-1993, the unnotched simply supported beam impact strength of the product was tested. The specific test results are shown in Table 1.

[0106] Table 1: Product performance test results

[0107] Tensile strength / MPa <![CDATA[Impact strength / kJ·m -2 > Example 1 35.5 76.2 Example 2 35.8 76.4 Example 3 36.2 76.7 Example 4 33.2 73.1 Example 5 36.3 76.9 Example 6 33.1 72.7 Example 7 32.6 70.4 Comparative Example 1 34.5 75.2 Comparative Example 2 30.2 68.1 Comparative Example 3 28.7 65.1

[0108] It can be seen from the test results in Table 1 that the product obtained by the present invention can obtain more excellent results when performing tensile and impact tests due to the uniform dispersion and strong interface interaction between the components.

[0109] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. An insulating plastic material, characterized in that: The invention comprises the following raw materials in parts by weight: 100-110 parts of polypropylene, 20-25 parts of polystyrene, 6-8 parts of micro-carbonized wood fiber; The preparation steps of the micro-carbonized wood fiber include: After washing the bagasse, drying, crushing, and passing through an 80-120 mesh sieve, bagasse crushed material is obtained; Ultrasonic dispersion of bagasse crushed materials in water, and then adding 8-10% of the weight of bagasse crushed materials with ethyl orthosilicate, after hydrolysis reaction, filtering, washing and drying to obtain a precursor; In an inert atmosphere, the precursor is slowly heated to 300-320° C. at a rate of 0.1-0.2° C. / min, and after being kept warm for 6-24 hours for micro-carbonization treatment, the material is discharged to obtain micro-carbonized wood fiber.

2. An insulating plastic material according to claim 1, characterized in that: The hydrolysis reaction includes, at a pH of 5.6-6.2, a temperature of 60-65° C., and a stirring rate of 60-80 r / min, and the hydrolysis reaction is carried out for 3-5 hours.

3. The insulating plastic material according to claim 1, characterized in that: The heat preservation micro-carbonization treatment time is 12-14 hours.

4. The insulating plastic material according to claim 1, characterized in that: The preparation step of the micro-carbonized wood fiber also includes: After soaking the bagasse in water, taking it out, and then letting it stand for natural fermentation for 5-10 days at a temperature of 35-40°C and a relative humidity of 80-85%, and then washing it with water, heating it to boil, and filtering it to obtain pretreated bagasse; The pretreated bagasse is washed, dried, crushed, and passed through a 80-120 mesh sieve to obtain bagasse crushed material; Ultrasonic dispersion of bagasse crushed materials in water, and then adding 8-10% of the weight of bagasse crushed materials with ethyl orthosilicate, after hydrolysis reaction, filtering, washing and drying to obtain a precursor; In an inert atmosphere, the precursor is slowly heated to 300-320° C. at a rate of 0.1-0.2° C. / min, and after being kept warm for 6-24 hours for micro-carbonization treatment, the material is discharged to obtain micro-carbonized wood fiber.

5. The insulating plastic material according to claim 1, characterized in that: The insulating plastic material further includes polyoxymethylene resin with a mass 0.6-0.8 times that of the polystyrene; Furthermore, when preparing the insulating plastic material, the raw materials are first mixed, heated to 158-160° C., high-viscosity blending for 10-12 minutes, then heated to 170-175° C., medium-viscosity blending for 4-6 minutes, and then heated to 215-220° C., low-viscosity blending for 10-15 minutes.

6. The insulating plastic material according to claim 1, characterized in that: The insulating plastic material also includes an additive in an amount of 4-6% by mass of the polypropylene; The auxiliary agent comprises the following raw materials in parts by weight: 10-15 parts of lubricant, 15-20 parts of antioxidant, 20-25 parts of antioxidant, 30-35 parts of plasticizer; Wherein, the lubricant is selected from any one of calcium stearate, magnesium stearate and zinc stearate; The antioxidant is selected from any one of antioxidant 4010, antioxidant RD, antioxidant MB, antioxidant D, antioxidant AW, and antioxidant BLE; The antioxidant is selected from any one of antioxidant BHT, antioxidant 801, butylated hydroxytoluene, and thiobis(3-methyl-6-tert-butyl)phenol; The plasticizer is selected from any one of tributyl citrate, epoxy soybean oil, dicyclohexyl phthalate, glycerol tribenzoate or trimethylolpropane tribenzoate.

7. The insulating plastic material according to claim 1, characterized in that: The insulating plastic material further includes organic bentonite in an amount 0.4-0.6 times the mass of the micro-carbonized wood fiber; Furthermore, when preparing the insulating plastic material, the steps include: First, the organic bentonite and the carbonized wood fiber are mixed and poured into water, and then ultrasonically treated for 40-60 minutes at an ultrasonic frequency of 200-220 kHz, and then filtered, washed, dried, passed through a 500-mesh sieve, and the finer particles under the sieve are sieved out to obtain the residue on the sieve to obtain a blend; After mixing the blend, polypropylene and polystyrene, heat to 158-160°C, blend for 10-12 minutes at high viscosity, then heat to 170-175°C, blend for 4-6 minutes at medium viscosity, then continue to heat to 215-220°C, blend for 10-15 minutes at low viscosity.

Citation Information

Patent Citations

  • Polypropylene wood plastic composite plate and preparation method thereof

    CN107286464A

  • Polypropylene composite material as well as preparation method and application thereof

    CN113308046A

  • High-oil-resistance polypropylene-polystyrene composite material as well as preparation method and application thereof

    CN117402439A

  • Composite Polymer Molded Product

    US20130206037A1

  • Wood plastic composites and manufacturing method thereof

    US20150119502A1